2004
DOI: 10.1110/ps.03496004
|View full text |Cite
|
Sign up to set email alerts
|

Modification of halogen specificity of a vanadium‐dependent bromoperoxidase

Abstract: The halide specificity of vanadium-dependent bromoperoxidase (BPO) from the marine algae, Corallina pilulifera, has been changed by a single amino acid substitution. The residue R397 has been substituted by the other 19 amino acids. The mutant enzymes R397W and R397F showed significant chloroperoxidase (CPO) activity as well as BPO activity. These mutant enzymes were purified and their properties were investigated. The maximal velocities of CPO activities of the R397W and R397F enzymes were 31.2 and 39.2 units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…a Phe397 in VCPO ( Figure 4B) replacing a histidine residue in VBPO, was responsible for the difference in halogen specificity [66]. Previously, the mutation of the arginine residue (Arg397) in the red algal VBPO from C. pilulifera ( Figure 4F) has conferred significant chloroperoxidase activity to mutant enzymes R397W and R397F [94,107]. This residue is replaced by a tryptophan residue in the fungal VCPO.…”
Section: Vo 4 Coordination In the Crystal Structure Of Vanadium Halopmentioning
confidence: 97%
“…a Phe397 in VCPO ( Figure 4B) replacing a histidine residue in VBPO, was responsible for the difference in halogen specificity [66]. Previously, the mutation of the arginine residue (Arg397) in the red algal VBPO from C. pilulifera ( Figure 4F) has conferred significant chloroperoxidase activity to mutant enzymes R397W and R397F [94,107]. This residue is replaced by a tryptophan residue in the fungal VCPO.…”
Section: Vo 4 Coordination In the Crystal Structure Of Vanadium Halopmentioning
confidence: 97%
“…The brominating activity of this mutant at pH 5 is increased ϳ6-fold to a k cat of 575 s Ϫ1 , which is one of the highest values for Br Ϫ turnover reported for a vanadium haloperoxidase. The chlorinating activity of the P395D/L241V/T343A mutant is ϳ2-fold higher than the wild-type enzyme, thereby making this the best chlorinating vanadium haloperoxidase (21,22).…”
Section: E Coli Expression System and Generation Ofmentioning
confidence: 99%
“…The assigned full positive charge on the protonated peroxide oxygen in VCPO was also suggested to give rise to the very strong uncompetitive inhibition by azide seen in VCPO, being absent in wild-type VBPOs (20). A VBPO mutant from C. pilulifera that essentially has become a VCPO was also strongly inhibited by azide (21). The His-411 of VBPO from A. nodosum also forms a hydrogen bond with the catalytically important Lys-341, and it was suggested that this decreases the polarizing effect of this histidine on the bound peroxide (15).…”
mentioning
confidence: 99%
“…The second step, i.e., the oxidation of the halide, is the determinant for the enzymatic specificity of VHPO but has yet to be elucidated. Targeted active site mutants of C. inaequalis VCPO or C. pilulifera and Gracilaria changii VBPO have shown drastic reductions or increases of chlorinating activity, respectively (20)(21)(22). According to these structure-function studies, the catalytic properties and halide specificities of VCPO and VBPO are likely to be dependent on the electronic environment around the VO 4 moiety (4,15,23).…”
mentioning
confidence: 94%